Perioperative administration of vedaprofen, tramadol or their combination does not interfere with platelet aggregation, bleeding time and biochemical variables in cats - Brondani, Juliana T. [UNESP]; Luna, Stelio P. L. [UNESP]; Marcello, Gracy C. G. [UNESP]; Padovani, Carlos R. [UNESP] (Elsevier B.V., 2009)
A randomized double blind and placebo controlled design was used to investigate the hemostatic, biochemical, gastrointestinal and behavioral effects of pre- and postoperative administration of vedaprofen 0.5 mg/kg PO (V), tramadol 2 mg/kg SC (T), their association (VT) or placebo (P) in 40 adult female cats (3.0 +/- 0.32 kg; 1.8 +/- 0.7 years) distributed in groups of 10. Platelet aggregation and bleeding time were measured before and 52 11 after ovariohysterectomy. Serum urea, creatinine, alanine aminotransferase, alkaline phosphatase and gamma-glutamyl transferase concentrations were measured before and 7 days postoperatively. The occurrence of vomiting, frequency and consistency of feces, and behavior were observed for 7 days postoperatively. Morphine (0.5 mg/kg, IM) was used as rescue analgesic. Laboratory variables did not change. Vomiting was observed only after morphine administration. Mild euphoria was observed in T and VT. The perioperative use of vedaprofen and/or tramadol did not modify the hemostatic, biochemical and gastrointestinal function in cats. (C) 2009 ESFM and AAFP. published by Elsevier Ltd. All rights reserved.